The Acute Optic Neuritis Network (ACON): Study protocol of a non-interventional prospective multicenter study on diagnosis and treatment of acute optic neuritis - Asseyer, Susanna; Asgari, Nasrin; Bennett, Jeffrey; Bialer, Omer; Blanco, Yolanda; Bosello, Francesca; Camos-Carreras, Anna; Carnero Contentti, Edgar; Carta, Sara; Chen, John; Chien, Claudia; Chomba, Mashina; et al. (Frontiers in Neurology, 2023)
Optic neuritis (ON) often occurs at presentation of multiple sclerosis (MS), neuromyelitis optica spectrum disorders (NMOSD) and myelin-oligodendrocyte-glycoprotein (MOG) antibody-associated disease (MOGAD). The recommended treatment of high-dose corticosteroids for ON is based on a North-American study population, which did not address treatment timing, or antibody serostatus. The Acute Optic Neuritis Network (ACON) presents a global, prospective, observational study-protocol primarily designed to investigate the effect of time to high-dose corticosteroid treatment on 6-month visual outcomes in ON. All patients presenting within 30 days of inaugural ON will be enrolled. For primary analysis, patients will subsequently be assigned either into the MS-ON, aquaporin-4-IgG positive ON (AQP4-IgG+ON) or MOG-IgG positive ON (MOG-IgG+ON) group and then further sub-stratified according to the number of days from onset of visual loss to high-dose corticosteroids (days-to-Rx). The primary outcome measure will be high-contrast best-corrected visual acuity (HC-BCVA) at 6 months. Additionally, multimodal data will be collected in subjects with any ON (CIS-ON, MS-ON, AQP4-IgG+ON or MOG-IgG+ON and seronegative non-MS-ON), excluding infectious and granulomatous ON. Secondary outcomes include: optical coherence tomography (OCT) and magnetic resonance imaging (MRI) measurements, serum and cerebrospinal fluid (CSF) biomarkers (AQP4- and MOG-IgG levels; neurofilament; glial fibrillary protein), questionnaires (headache, visual function in daily routine, depression, and quality of life) at presentation, at 6- and 12-months follow-up. Data will be collected from 26 academic hospitals from Africa, Asia, the Middle East, Europe, North America, South America, Australia and Europe. Planned recruitment consists of 100 MS-ON, 50 AQP4-IgG+ON and 50 MOG-IgG+ON. This prospective, multimodal data collection will assess the potential value of early high-dose corticosteroid treatment, investigate the interrelations between functional impairments and structural changes, and evaluate the diagnostic yield of laboratory biomarkers. This analysis has the ability to substantially improve treatment strategies and accuracy of diagnostic stratification in acute demyelinating ON. Trial Registration: ClinicalTrials.gov Identifier: NCT05605951